2008
DOI: 10.1158/0008-5472.can-07-5046
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 9 Is a Mediator of Epidermal Growth Factor–Dependent E-Cadherin Loss in Ovarian Carcinoma Cells

Abstract: Epidermal growth factor (EGF) receptor (EGFR) is frequently elevated in epithelial ovarian cancer, and E-cadherin expression is often reduced in advanced disease. In this study, we investigated a mechanism by which EGFR activation promotes disruption of adherens junctions through induction of matrix metalloproteinase 9 (MMP-9). We show that EGFR activation down-modulates E-cadherin, and broad spectrum MMP inhibition ameliorates EGF-stimulated junctional disruption and loss of E-cadherin protein. MMP-9 involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 44 publications
8
103
0
Order By: Relevance
“…among MMP subtypes, MMP-9 is closely associated with poor outcome in ovarian cancer (22) and its expression level is significantly stronger as lesions progressed from a benign tumor to advanced carcinoma (23,24). earlier study showed that MMP-9 overexpression led to a loss of e-cadherin and promoted a migratory and invasive phenotype in ovarian cancer cells (25), supporting the present results. on the other hand, in this study, although Vegf-c expression was decreased in the cBr1-Dna tumors, its expression in cBr1-sirna tumors was similar to that of the control ovarian cancer cell tumors.…”
Section: Altered Expression Of Vegf-c E-cadherin and Mmp-9 In The Tsupporting
confidence: 85%
“…among MMP subtypes, MMP-9 is closely associated with poor outcome in ovarian cancer (22) and its expression level is significantly stronger as lesions progressed from a benign tumor to advanced carcinoma (23,24). earlier study showed that MMP-9 overexpression led to a loss of e-cadherin and promoted a migratory and invasive phenotype in ovarian cancer cells (25), supporting the present results. on the other hand, in this study, although Vegf-c expression was decreased in the cBr1-Dna tumors, its expression in cBr1-sirna tumors was similar to that of the control ovarian cancer cell tumors.…”
Section: Altered Expression Of Vegf-c E-cadherin and Mmp-9 In The Tsupporting
confidence: 85%
“…This work may have clinical significance given that the ovarian tumor environment contains numerous EGFR activators 2 and approximately 35% of all ovarian cancer tumors are positive for activated EGFR. 3,4 Using an in vitro paradigm of EGF exposure of OVCA 433 cells, we found that acute and long-term EGFR activation increases DNMT activity. It is important to note the observed increase in DNMT activity is an increase in total DNMT activity and does not distinguish the relative contributions of the maintenance methyltransferase (DNMT1) or de novo methyltransferases t-test showed a significant increase in DNMt activity in HS68 cells treated with 10 nM EGf, n = 3.…”
Section: Discussionmentioning
confidence: 96%
“…2 The presence of these activators in patient ascites suggests that the tumor microenvironment is under chronic EGFR activation and may account for the observation that approximately 35% of all ovarian cancer tumors are positive for activated EGFR (tyrosine phosphorylated EGFR). 3,4 Overexpression of EGFR, and its ligands, has been detected in ovarian tumors and correlates with poor prognosis. 3,5,6 EGFR is a member of the receptor tyrosine kinase family that possesses intrinsic tyrosine kinase activity.…”
Section: Introductionmentioning
confidence: 99%
“…The ligands for the epidermal growth factor receptor (EGFR) are potent drivers of cell proliferation and are regulators of tissue homeostasis. Malfunction of molecules in this system is observed in breast cancer and other malignancies [256,257]. Evidence has revealed a potential role of ADAM proteinases in the regulation of the EGFR pathway.…”
Section: Matrix Mellalloproteinases (Mmps)mentioning
confidence: 99%